Dry spells in a semi-arid region of Brazil and their influence on maize productivity - Nogueira, Danilo B.; da Silva, Alexsandro O.; Giroldo, Aelton B.; da Silva, Ana P.N.; Costa, Bruno R.S. [UNESP] (Elsevier, 2023)
Maize production (Zea mays) under rainfed conditions, although risky in semi-arid areas, is still widespread. In theses areas, rainfall events are concentrated over a short, irregular and discontinuous period, so that understanding these events has great relevance to the anning and agricultural management of maize. This study sought to understand the relationship between the frequency of different classes of dry spells formed during the rainy season and the occurrence of dry, normal and wet years in the semi-arid region. Also analysed was whether this same frequency is influenced by the incidence of long-duration El Niño and La Niña phenomena, and how all these factors interfere with maize productivity. For this, a trend analysis was then carried out between the frequency of dry spells, considering years classified as dry, normal and wet, and whether this number is also influenced by the occurrence of long-duration El Niño and La Niña events, and how the classes and temporal occurrence of dry spells influence maize productivity within the study region. The results show that crop achieving good results for dry spells of up to 15 days, after which productivity falls significantly. The greatest number of dry spells was found in regions of the semi-arid sertão that are further inland, especially more prolonged dry spells. Throughout the region, the highest probability of occurrence of dry spells is during the first and last month of the rainy season, with a high concentration of dry spells which vary from 6 to 20 days with no rain, indicating the need supementary irrigation, anting nearer the end of the season in years of normal or wet conditions, reducing the chances of the crop suffering from water stress.
Keywords: Climate condition; El niño; La niña; Rainfall scenarios; Rainfed